2014
DOI: 10.1016/j.jagp.2013.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Executive Function in Contemplated and Attempted Suicide in Late Life

Abstract: Objective Executive deficits may play an important role in late-life suicide. Yet, current evidence in this area is inconclusive and does not indicate whether these deficits are broadly associated with suicidal ideation or specific to suicidal behavior. This study examined global cognition and specifically executive function impairments as correlates of suicidal ideation and suicidal behavior in depressed older adults, with the goal of extending an earlier preliminary study. Design Case-control study. Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 30 publications
5
49
1
Order By: Relevance
“…Gujral et al (2013) examined global cognition and executive function as correlates of suicidal ideation and suicidal behavior in depressed older adults. Both suicide attempters and suicide ideators performed worse on the Executive Interview (EXIT; Royall et al 1992) compared to non-suicidal depressed or non-psychiatric control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Gujral et al (2013) examined global cognition and executive function as correlates of suicidal ideation and suicidal behavior in depressed older adults. Both suicide attempters and suicide ideators performed worse on the Executive Interview (EXIT; Royall et al 1992) compared to non-suicidal depressed or non-psychiatric control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate performance of suicide ideators in the current sample suggests a dose-response relationship between cognitive control deficits and the progression of the suicidal process. This dose-response relationship, however, was lacking in our previous analysis of a screening measure of cognitive control, EXIT25, in a larger, overlapping sample of older adults (Gujral et al, 2012), where suicide ideators performed as poorly as suicide attempters.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to impulsive aggression (McGirr and Turecki, 2007) and persistent hopelessness (Beck et al, 1985, Szanto et al, 1998, several studies have now reported impairments in cognitive domains such as attentional/cognitive control, episodic memory, working memory, and language fluency (Keilp et al, 2013, Keilp et al, 2001, Raust et al, 2007, Richard-Devantoy et al, 2012 as well as in decision-making (Clark et al, 2011, Dombrovski et al, 2010, Jollant et al, 2005. Cognitive impairments may be particularly prominent in elderly suicide attempters (Dombrovski et al, 2008a, Dombrovski et al, 2010, Erlangsen et al, 2008, Gujral et al, 2012, McGirr et al, 2012. Age-related decline in cognitive control (Amieva et al, 2004, Drag et al, 2010 may be among the factors contributing to the increasing suicide rates in old age (Dombrovski et al, 2008b, Erlangsen et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Executive deficits are broadly associated with suicidal preoccupation in older depressed adults but do not directly facilitate suicidal behavior (Gujral et al, 2014). Fundamental deficits in attention process may play a role in suicidal behavior risk.…”
Section: Focus Of Attentionmentioning
confidence: 98%